NIRS Database on fresh blended cassava for Dry Matter, Water absorption, Texture & cooking Time at CIAT, Colombia - Tran, Thierry; Belalcazar Martinez, John Eiver; Davrieux, Fabrice (2023)
This database contains 250 NIR spectra of cassava puree acquired in CIAT (Colombia), by using FOSS DS2500 NIR spectrometer. Cassava harvested at CIAT (Colombia) from various fields and years: - 2019-2020: 2 fields ""parentales/progenitors"" and ""sensorial"" in November 2019-February 2020. Five harvests (trials): 19-63, 19-64 & 20-02 are from the field parentales in 11/2019, 12/2019 and 01/2020 (9, 10, 11 months after planting), respectively; and 20-03 & 20-11 from field sensorial in 01/2020 and 02/2020 (10 and 11 months after planting) - 2021: 1 field ""progenitors"" in January-March 2021. 3 harvests (trials): 21-01, 21-04 (complement 21-05) & 21-09 in January, February and March (9, 10, 11 months after planting).